MWSN modeling using OMNeT++ simulator - Shaukat, Haafizah Rameeza; Hashim, Fazirulhisyam (IEEE, 2014)
The Mobile Wireless Sensor Network (MWSN) plays an important role in many applications and activities and we have presented our experience to design the MWSN which execute the realistic explanation by using OMNeT++. The simulation is based on proper selection and estimated parameters for generating and establishing better performance. A detailed analysis of the design using OMNet++ (MiXiM Framework) helped in depth understanding of the network and has resulted into a better MWSN design. In this paper, we also discuss in detail the mobile nodes architecture, mobile nodes movement at different time interval and evaluate the results for the simple scenario of MWSN.